RETRACTED: The synergistic effect of innovation transfer in the agricultural sector: Regional aspect - Barmuta Karine; Akhmetshin Elvir; Kharchenko Sergey; Matjonov Bekjon (BIO Web of Conferences)
See the retraction notice BIO Web of Conferences 116, 00001 (2024), https://doi.org/10.1051/bioconf/202411600001